2020
DOI: 10.1021/acs.jced.0c00221
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Diffusivity Measurement of Trans-1-chloro-3,3,3-trifluoropropene (R1233zd(E)) and Dodecafluoro-2-methylpentan-3-one (Novec1230) by the Dynamic Light Scattering Method

Abstract: In this work, we have studied the thermal diffusivity of saturated liquids in the temperature range from 303.15 to 393.15 K for trans-1-chloro-3,3,3-trifluoropropene (R1233zd­(E)) and dodecafluoro-2-methylpentan-3-one (Novec1230) by the dynamic light scattering method. The relative combined uncertainties of thermal diffusivity were estimated to be 3%. The liquid thermal diffusivity was correlated with a simple polynomial equation. The deviations between our experimental results and the correlation are less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Miyara et al 5 investigated the viscosities of R-1233zd(E) using a tandem capillary tube method. Tang et al 6 measured the thermal diffusivities of R-1233zd(E) between (303.15 and 393.15) K using a dynamic light scattering method. Lago et al 7 presented speeds of sound for liquid R-1233zd(E) from (273.15 to 353.15) K and pressures of up to 35 MPa by means of the double pulse−echo method.…”
Section: Introductionmentioning
confidence: 99%
“…Miyara et al 5 investigated the viscosities of R-1233zd(E) using a tandem capillary tube method. Tang et al 6 measured the thermal diffusivities of R-1233zd(E) between (303.15 and 393.15) K using a dynamic light scattering method. Lago et al 7 presented speeds of sound for liquid R-1233zd(E) from (273.15 to 353.15) K and pressures of up to 35 MPa by means of the double pulse−echo method.…”
Section: Introductionmentioning
confidence: 99%
“…Miyara et al 10 measured the vapor and liquid viscosities by a tandem capillary tubes method. Tang et al 11 studied the thermal diffusivities of saturated liquid of R-1233zd(E) from (303.15 to 393.15) K using a dynamic light scattering method. Fedele et al 12 reported 94 liquid density points from (283.15 to 363.15) K and 60 pvT points from (308.15 to 373.15) K. Di Nicola et al 13 presented 81 vapor pressure data points between (234.15 and 375.15) K. Romeo et al 14 also measured the liquid-phase densities of R-1233zd(E) between (273.15 and 333.15) K at pressures within 30 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fire extinguishing agents have been replaced by eco-friendly materials, such as HFC-227ea and FK-5-1-1-12, which have a low global warming potential (GWP) and an ozone depletion potential close to almost 0. However, these eco-friendly fire extinguishing agents are difficult to store and utilize due to the low vaporization temperature and high vapor pressure [ 4 , 5 , 6 ]. In order to overcome these disadvantages, methods of using an aerosol system [ 7 ] and encapsulating the fire extinguishing agent with a polymeric material have been proposed [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%